IN SILICO MOLECULAR MODELING AND DOCKING OF APIGENIN AGAINST THE LUNG CANCER CELL PROTEINS - Kasilingam, Tulasi; Elengoe, Asita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In this study, three-dimensional (3D) structures of lung cancer cell line proteins (cellular tumor antigen [p53], caspase 3, and mucosal addressin cell adhesion molecule 1) were generated, and their binding affinities with apigenin through local docking were studied. Methods: The lung cancer cell line proteins were built using Swiss model and visualized by the PyMol software. The physicochemical characterization of the protein models was evaluated by Expasy's ProtParam Proteomics server. Then, they were validated by PROCHECK, ProQ, ERRAT, and Verify 3D programs. Finally, the protein models were docked with apigenin using BSP-Slim server. Results: All the protein models were acceptable and of good quality. The apigenin showed the binding energy with cellular tumor antigen (p53), caspase 3, and mucosal addressin cell adhesion molecule 1 at −4.611, −5.750, and −5.307 kcal/mol, respectively. Conclusion: The caspase 3 had the strongest bond with apigenin. These potential drug candidates can further be validated in laboratory experiments for its proper function.